Man [videorecording] the incredible machine (The Society, 1976)
An exposition on the design and adaptability of the human body. Witness the strength, beauty and grace of the body. Probes the mechanisms of the senses, looking into the workings of the eyes, ears and vocal cords. Includes early x-ray motion pictures of the skeleton and joints, muscular arrangement and the pumping and fluttering of lungs and heart. Another segment of this film concerns the workings of the mind.